Ciranda na arte, construindo performances, afetos e liminaridades. Experiências arte/educativas na rede pública do Estado de Goiás (2009-2016) - Alcantara, Luz Marina de (2020)
This study analyzes the performances of Ciranda da Arte Center of Study and Research, an institution of the State of Goiás, with no similar at the national level, founded on July 15th, 2005. Ciranda aims to develop a process of continuing education in art, focusing on artistic production, research and training of art/educators. Ciranda looks for updating and deepening knowledge that reverberates in the quality of art teaching in the system of state public school and the aesthetic education of society in general (PPP 2015). Therefore, we examine the historical path of art teaching in the public network of Goiás developed under the intervention of Ciranda da Arte, historically considering the eleven years before its creation and the eleven years that followed (1994-2016). As a theoretical framework, the performances were produced according to the concepts of affectivity and significant learning developed by the French philosopher and psychologist Henri Wallon (1879-1962), and also the American philosopher John Dewey (1859-1952). From the cultural performance perspective, the current study tries to understand the relational game of the ciranda performances as processes of structure, anti-structure and liminalities, concepts developed by Victor Turner (1920-1983) in his book The Ritual Process. Structure and Anti-structure (Lewis H. Morgan Lectures, 1966). I also adopted the sequence of artistic performance as it was developed by Richard Schechner (1934) for the analysis of the collective and individual art exhibitions of the full-time state schools in the cities of Anápolis, Goiânia, Inhumas and Palmeiras de Goiás.